2018
DOI: 10.1021/acssuschemeng.8b02001
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Noble-Metal-Free Co-NG/TiO2 Photocatalyst for H2 Evolution: Synergistic Effect between Single-Atom Co and N-Doped Graphene for Enhanced Photocatalytic Activity

Abstract: Photocatalytic water splitting for H2 evolution is appealing for transforming solar energy into clean chemical fuel. This technique generally requires noble metals as H2 evolution cocatalysts to facilitate efficient cleavage of water. Herein, we report a noble-metal-free TiO2 nanobelts composite photocatalyst, in which TiO2 nanobelts are supported by nitrogen-doped graphene coordinated with a single Co atom (Co-NG). The results show that Co-NG is an efficient cocatalytst for the photocatalytic H2 production ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 63 publications
0
54
0
Order By: Relevance
“…Yi et al [118] synthesized a composite in which TiO 2 nanobelts were supported by N-doped graphene (NG) coordinated with a single Co atom to replace noble metals with a cost-effective photocatalyst. Under simulated solar irradiation ( Figure 14), e − /h + pairs are formed.…”
Section: Tio 2 -G/go/rgomentioning
confidence: 99%
“…Yi et al [118] synthesized a composite in which TiO 2 nanobelts were supported by N-doped graphene (NG) coordinated with a single Co atom to replace noble metals with a cost-effective photocatalyst. Under simulated solar irradiation ( Figure 14), e − /h + pairs are formed.…”
Section: Tio 2 -G/go/rgomentioning
confidence: 99%
“…Combining single‐atomic sites into 2D ultrathin nanosheets is a promising approach to integrate their advantages. [ 453 ] Di et al [ 454 ] reported the successful synthesis of Bi 3 O 4 Br atomic layers with well‐dispersed single cobalt atoms (Figure 28c). It was proven that the valence state of isolated and highly dispersed single Co atom is close to +2 (Figure 28d,e), because the position of Co K‐edge absorption edge was close to that of CoO rather than Co foil in Co–Bi 3 O 4 Br–1.…”
Section: New Trends and Strategiesmentioning
confidence: 99%
“…In recent years, the atomic-scale con gurations of single-sites have been developed, i. e. single-atom, single-metal-atom-oxide and single-unit-cell [60][61][62][63]. Following this route for TiO 2 , potential active sites can be designed as a single site anchored on TiO 2 surface [64][65][66][67][68][69][70][71][72][73][74][75], and atomic step site on TiO 2 has been veri ed to enhance electron-transfer and molecular capture capability [76][77][78][79][80] .…”
Section: Introductionmentioning
confidence: 99%